2011
DOI: 10.1002/cphc.201100080
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Functionalization of Gold Surfaces and Protein Adsorption by PM‐IRRAS

Abstract: The control of morphology and coating of metal surfaces is essential for a number of organic electronic devices including photovoltaic cells and sensors. In this study, we monitor the functionalization of gold surfaces with 11-mercaptoundecanoic acid (MUA, HS(CH(2) )(10) CO(2) H) and cysteamine, aiming at passivating the surfaces for application in surface plasmon resonance (SPR) biosensors. Using polarization-modulated infrared reflection-absorption spectroscopy (PM-IRRAS), cyclic voltammetry, atomic force mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
(64 reference statements)
0
6
0
1
Order By: Relevance
“…This allowed the simultaneous measurements of spectra for the two polarizations, and their difference provides surface-specific information, while their sum provides the reference spectrum (buffer with or without antimycobacterial compound). In this work, PM-IRRAS was elected due to the advantages over the conventional IRRAS mode, namely the independence of modulated reflectivity of the isotropic adsorption from the vapor or bulk water, overcoming the problem of the surrounding water vapor [36,37].…”
Section: Polarization-modulation Infrared Reflection Spectroscopymentioning
confidence: 99%
“…This allowed the simultaneous measurements of spectra for the two polarizations, and their difference provides surface-specific information, while their sum provides the reference spectrum (buffer with or without antimycobacterial compound). In this work, PM-IRRAS was elected due to the advantages over the conventional IRRAS mode, namely the independence of modulated reflectivity of the isotropic adsorption from the vapor or bulk water, overcoming the problem of the surrounding water vapor [36,37].…”
Section: Polarization-modulation Infrared Reflection Spectroscopymentioning
confidence: 99%
“…This peak decrease in absorption at 1650 cm −1 was attributed to the loss of carbonyl groups (C=O) with the enzyme attachment. The peak at 2300 cm −1 is characteristic of O-H stretching of carboxylic acid [13]. The PM-RAIS spectra confirmed that amine 3, characteristic of the enzyme, reacted with the NHS active esters, resulting in a modification of the peak at 2350 cm −1 .…”
Section: Characterization Of the Nanobiosensor Surfacementioning
confidence: 68%
“…PM-IRRAS was used due its advantages over the conventional IRRAS mode, namely, the independence of the modulated reflectivity of the isotropic adsorption from bulk water or water vapor, which allows the problem of the surrounding water vapor to be overcome. [21,23] …”
Section: Langmuir Isothermsmentioning
confidence: 98%
“…[21,47] Moreover, PM-IRRAS allows monitoring of the vibrational spectra of the characteristic head groups of the phospholipids, such as phosphate and carbonyl present at the air/solution interface during compression of the monolayer. [21,23] The band positions of the asymmetric phosphate and carbonyl stretching vibrations in the EPC:CHOL monolayer in the absence and presence of the antimycobacterial compounds are listed in Table 2. Analysis of the phosphate and carbonyl bands is of special interest and allowed the interactions of the antimycobacterial compounds with the polar phospholipid head groups to be monitored.…”
Section: Polarization-modulated Infrared Reflection-absorption Spectrmentioning
confidence: 99%